L2 Writing Proficiency and Mastery of Complex Sentence: A Study of Indonesian English Education Major University Students - Adaninggar Septi Subekti (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2018)
This study investigated the extent of learners’ mastery of complex sentences in predicting L2 writing proficiency. This study used forty essays of ten students of English Education Department. It found that complex sentences became the most frequently written sentences in the analysed essays. The mean of their level of mastery was 57.58%, suggesting that their mastery in general was quite low. Furthermore, learners’ number of complex sentences did not have any significant relationship with L2 writing proficiency, r (40) = -.08, p > .05, but their level of mastery of complex sentences positively correlated with their writing proficiency, r (40) = .44, p < .01, suggesting that number of complex sentences regardless of grammaticality did not significantly correlate with L2 writing proficiency and only grammatically correct complex sentences, seen through learners’ mastery, had positive correlation with L2 writing proficiency. Furthermore, learners’ mastery of complex sentences could predict 19% of their writing proficiency, R2 = .19. From the results, implications and limitations of the study as well as suggestions on future studies were stated.Keywords: L2 writing proficiency, complex sentences, mastery